Bahasa Roh dan Spiritualitas Perikoresis dalam Peristiwa Pentakosta: Analisis Reinterpretatif Kisah Para Rasul 2:1-13 - Siahaan, Harls Evan R. (Sekolah Tinggi Teologi Berea, Salatiga, 2021)
Speaking in tongues has been understood as a sign of the baptism of the Holy Spirit by the Pentecostal churches referring to the narrative of Acts 2:1-13. There is a negative tendency in articulating tongues as a sign of being fulfilled with the Holy Spirit. This is a qualitative study of literature using a descriptive reinterpretative analysis method, which aims to find the essentials in the baptism of the Holy Spirit through rereading the narrative of the Pentecost event. The results of the study found the spirituality of perichoresis in the event followed by the phenomenon of speaking in tongues. In conclusion, speaking in tongues which occurred in the event of Pentecost is a reflection of the spirituality of perichoresis of people being filled with the Holy Spirit.Abstrak Bahasa roh selama ini dipahami sebagai tanda baptisan Roh Kudus oleh kelompok Pentakostal mengacu pada narasi Kisah Para Rasul 2:1-13. Ada tendensi negatif dalam mengartikulasikan bahasa roh sebagai tanda kepenuhan Roh Kudus. Kajian ini merupakan penelitian kualitatif literatur dengan metode deskripsi analisis reinterpretatif, yang bertujuan untuk menemukan hal esensial dalam baptisan Roh Kudus melalui pembacaan ulang narasi peristiwa Pentakosta. Hasil kajian mendapatkan spirtuallitas perikoresis dalam peristiwa yang diikuti fenomena bahasa roh tersebut. Kesimpulannya, bahasa roh dalam peristiwa Pentakosta merupakan refleksi spiritualitas perikoretik dipenuhi Roh Kudus.